(untitled) (Research, Society and Development, 2020)
The objective of this study was to produce salami with and without the addition of starter cultures and to evaluate their effect on the sensory, physical and microbiological characteristics of the products. Three treatments of Italian type salami were elaborated: T1 (control - without addition of starter culture); T2, product with addition of starter cultures Lyocarni RHM-33 (Pediococcus pentosaceus and Staphylococcus xylosus) and T3 with addition of starter cultures Lyocarni SBM-11 (Staphylococcus xylosus, Staphylococcus carnosus, and Lactobacillus sakei). The count of lactic acid bacteria in the inoculated products at the end of the 21st day of processing was 2.9 x 106 CFU/g, and 3.2 x 105 CFU/g, for treatments 2 and 3 respectively. The total coliform and thermotolerant count was not affected (P>0.05) by the interaction between treatments. The presence of starter cultures in the treatments did not affect the luminosity index (L*) and yellow index (b*) in relation to the control treatment (p>0.05). or red index and saturation, Treatment 2 presented higher values (P<0.05). Only the hardness and chewability parameters were affected (p<0.05) by the addition of starter cultures. The data obtained with the sensory analysis showed that the T2 treatment was the best accepted among the salami produced, for the attributes of taste, texture and overall impression. Thus, this work showed that the physical, microbiological and sensory aspects should be studied in depth for the choice of starter cultures, because the interaction of microorganisms interfere in the technological aspects of the products.